United Republic of Tanzania : Staff Assessment of Qualification for the Multilateral Debt Relief Initiative. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Tanzania reached the completion point under the enhanced HIPC Initiative on November 21, 2001. Staff is of the view that all criteria have been met, and recommends that the Board determine that Tanzania qualifies for immediate debt relief under the MDRI.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fund Arrangement; GDP; Government Commitment; PP; Second Generation PRSP; Tanzania, United Republic of